Development of Ankle-Foot Orthosis with Vibration Stimulator using Energy Harvesting Source for Cerebral Palsy Children - Jung, Do-Young; Yun, Sung-Joon; Kim, Young-Sun (International Journal of Engineering and Technology, 2018)
Background/Objectives: Recently, studies on the effects of vibration stimulation on the stiffness, strength, motion function, gait, and various daily activities have been conducted in patients with nervous diseases like Parkinson's disease, stroke, cerebral palsy (CP) and human multiple sclerosis(MS).Methods/Statistical analysis: Although a variety of ankle-foot orthosis (AFO) is generally used to increase the efficiency of gait and normalize movement patterns with spastic CP in clinic, it was no AFO combined with vibration stimulator to improve the gait. Therefore, we aim to develop AFO that can give local vibration stimuli to improve walking of children with CP.Findings: Therefore, it is possible to expect smooth gait and posture maintenance ability by applying vibration stimulus while wearing a short leg support, regardless of time and place when walking or standing.Improvements/Applications: The vibration stimulator uses a vibration motor equipped with an eccentric rotor. The power source of the vibration stimulator is combined with the energy harvesting technique using the piezoelectric element.Â Â